Revitalisasi Kearifan Lokal Minangkabau Dalam Pelaksanaan Program Sekolahadiwiyata Di Sumatera Barat - Dwi Astuti (Jurnal Pembangunan Nagari, 2017)
The program grabs adiwiyata program is part of the of environmental education school based on school , that is oriented toward the effort to enhance the knowledge environment in a bid to settle the existing environmental problems more complex .This study descriptive nature of the decrees issued based on the qualitative , the technique of the collection of data deal is the objective of the interview and the tracing documents .The results of the study show that the program grabs adiwiyata school got a when he is a part the national program for rural but has experienced a fall in when the program was delegated to schools as a program mandiri has been somewhat successful. The decline caused by various for , : environmental awareness not woke up , application of the system certification bustle and teachers with activities the fulfillment of standard teaching hours , the curriculum does not support , initiative leaders , and support human resources and the funds .To in overcome it projected can be built back when empower local knowledge minangkabau based on two the concept , namely budi is a basis of value understanding its natural environment while the concept of self-esteem as the base work ethic hard for achievement and progress in all sectors in life